The Transformation of Public Sector Accounting in Encouraging Improvement of Public Service Quality - Bashiruddin Ahmad; Haliah Haliah; Andi Kusumawati (International Journal of Economics and Management Sciences, 2024)
The transformation of public sector accounting is critical for enhancing the quality of public services. This evolution is driven by the need for greater transparency, accountability, and efficiency within government operations. Traditional accounting practices, often characterized by a focus on compliance and financial reporting, are being replaced by more comprehensive frameworks that emphasize performance measurement and management. This shift is largely influenced by globalization, technological advancements, and the increasing expectations of citizens for improved public services. By adopting modern accounting practices, public sector organizations can better align their financial management strategies with service delivery goals, thus fostering a culture of continuous improvement. Key elements of this transformation include the integration of performance indicators into accounting systems, the use of budgeting as a tool for strategic planning, and the implementation of accrual accounting. These practices facilitate more nuanced understanding of the resources used in delivering services and the outcomes achieved. Moreover, the adoption of digital technologies in accounting processes enhances data accessibility and enables real-time reporting, which supports informed decision-making. Ultimately, the transformation of public sector accounting is not merely a technical change but a fundamental shift in how public organizations operate. By focusing on outcomes and accountability, this transformation encourages  more responsive and efficient public service, thereby improving the overall quality of services provided to citizens.